Environmentally Friendly Waqf Model: A Response to Sustainable Economic Development and the Presence of a Circular Economy - Swadia Gandhi Mahardika; Afifa Tanweer (IAIN Syekh Nurjati Cirebon, 2025)
The excessive utilization of natural resources and the accumulation of waste pose serious challenges to sustainable development. The circular economy has emerged as a viable solution by emphasizing the reuse and recycling of materials. This study explores the significance of sustainable development and the necessity of a circular economy in achieving it. Effective waste management plays a crucial role in environmental protection and enhances living standards. In this context, waqf can contribute to environmental sustainability through the concept of green waqf. This study employed the literature review method to identify, review, evaluate, and synthesize relevant research on the phenomenon of interest and related research questions. By implementing the literature review approach, journal articles were systematically reviewed, and each process followed predetermined steps and procedures. The findings revealed that the proposed green waqf model consisted of five stages. First, the waqif transfers cash waqf to a waqf institution (nazir). Second, the nazir allocates waqf funds to establish a training center equipped with waste management technology to enhance human resource development. Third, the nazir, through the training center, provides skill development programs to empower beneficiaries (mauquf 'alaih). Fourth, beneficiaries are expected to secure employment and increase their productivity after completing the training. Fifth, continuous monitoring and evaluation must be conducted to ensure ongoing improvements. Ultimately, the proposed green waqf model is expected to contribute to both economic and environmental sustainability.